Manajemen Emosi Perspektif Tafsir Al-Qurthubi: Telaah Kisah Maryam dalam QS. Maryam: 23–26 - Siti Aminah Rambe; M. Jamil (Aksioreligia, 2026)
Anxiety and social pressure have become increasingly prominent mental health concerns in modern society, particularly among individuals vulnerable to stigma originating from their social environment or internalized as self-stigma. The Qur’an, through the story of Maryam in QS. Maryam [19]: 23–26, offers a relevant model of emotion management. However, its psychological dimensions, particularly in Tafsir Al-Qurthubi, have not been sufficiently explored. This study aims to analyze Al-Qurthubi’s interpretation of QS. Maryam [19]: 23–26 as a framework for Qur’anic-based emotion management. This library research employs a descriptive-analytical qualitative approach. The primary source is Al-Jami’ li Ahkam Al-Qur’an by Al-Qurthubi, while Tafsir Al-Mishbah by M. Quraish Shihab and relevant literature on psychology and emotion management serve as secondary sources. The data were analyzed thematically by identifying the stages of Maryam’s emotional recovery. The findings reveal four stages: emotional validation, calming through concrete reassurance, active involvement through effort, and holistic fulfillment of physical and psychological needs accompanied by self-protection. These stages lead Maryam toward acceptance and trust in Allah. This study confirms that the story of Maryam is not merely a theological narrative about the miraculous birth of Prophet Isa, but also an applicable Qur’anic psychological model for contemporary Muslims confronting social and psychological pressures.